Modifikasi Pencerna Anaerobic - Syn, Yang Leong (Universiti Sains Malaysia, 2000)
Research on renewable energy process is carried out nowadays. The renewable energies include solar energy, wind energy, biomass energy and nuclear energy. Biomass sources estimated about 1800 billion tonnes[Biomass Handbook, Osamu Kitani & Carl 1989] is an efficient altenative energy. It has been used by human for a long time ago. Biomass is an organic matter consists of domestic waste, industrial waste and etc. biomass can be converted into fuel for generating electricity, heat and etc. Anaerobic digestion is a process to produce methane gas from biomass. Anaerobic digestion is process of bacteria digestion in the absence of oxygen. This method becomes popular in Malaysia since there are a lot of biomass sources like rubish, kitchen waste, animals waste and etc. This method can produce high quality of biogas contain about 55-65% of methane and it can be widely used for cooking, operating engine and etc. The main objective of this project is to modified the existing anaerobik digester to increase biogas production. The existing digester can produce up to 48.5% of methane. Modifications include biogas recirculation of biogas, heating the digester slurry and to make mixing process more efficient. Biogas storing tank has to be prepared for biogas storing.